2006
DOI: 10.1111/j.1440-1630.2006.00538.x
|View full text |Cite|
|
Sign up to set email alerts
|

The effects of contextual relevance and ownership on a reaching and placing task

Abstract: Aim: This study investigated whether a more familiar environment and object ownership would result in enhanced motor performance. Methods: Thirty-two women from the community aged 30 to 60 years lifted and placed their mug and a second mug they did not own in their home kitchen and in a laboratory. Results: Although no differences were found on the factor of location, participants were more efficient (i.e. less movement time) when reaching for their own mug. Additionally, there were fewer movement units with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…Characteristics of the studies and main results are presented in Table 4. The purposeful activities used in the studies included: personal care (Taylor et al, 2018); writing (Ross & Nelson, 2000;Wu et al, 1994); eating (Hall & Nelson, 1998); using chopsticks (Ma et al, 1999;Rice et al, 2009); reaching for candy (Sackaloo et al, 2015), a mug (Holubar & Rice, 2006;Rice et al, 2009), a bell (Lin et al, 1998;Morton et al, 1992) or a magazine (Rice & Renock, 2006); meal preparation tasks (e.g., slicing vegetables or making cookies) (Fasoli et al, 2002;Hoppe et al, 2008;Miller & Nelson, 1987;Rice et al, 1999;Wu et al, 1998); woodwork or handcrafts (Bakshi et al, 1991); and board or computer games, throwing darts or ping-pong (Kehoe & Rice, 2016;King, 1993;Steinbeck, 1986;Wagner et al, 1995).…”
Section: Purposeful Activities and Motor Performance Outcomesmentioning
confidence: 99%
See 3 more Smart Citations
“…Characteristics of the studies and main results are presented in Table 4. The purposeful activities used in the studies included: personal care (Taylor et al, 2018); writing (Ross & Nelson, 2000;Wu et al, 1994); eating (Hall & Nelson, 1998); using chopsticks (Ma et al, 1999;Rice et al, 2009); reaching for candy (Sackaloo et al, 2015), a mug (Holubar & Rice, 2006;Rice et al, 2009), a bell (Lin et al, 1998;Morton et al, 1992) or a magazine (Rice & Renock, 2006); meal preparation tasks (e.g., slicing vegetables or making cookies) (Fasoli et al, 2002;Hoppe et al, 2008;Miller & Nelson, 1987;Rice et al, 1999;Wu et al, 1998); woodwork or handcrafts (Bakshi et al, 1991); and board or computer games, throwing darts or ping-pong (Kehoe & Rice, 2016;King, 1993;Steinbeck, 1986;Wagner et al, 1995).…”
Section: Purposeful Activities and Motor Performance Outcomesmentioning
confidence: 99%
“…Ten studies measured percentage of movement time to reach or maintain peak velocity, but only five studies found statistically significant differences. Movement time was measured in 13 studies, with eight studies reporting quicker movement during the purposeful activity condition (Fasoli et al, 2002;Holubar & Rice, 2006;Lin et al, 1998;Rice et al, 2009;Ross & Nelson, 2000;Sackaloo et al, 2015;Wu et al, 1994) or virtual reality (Kehoe & Rice, 2016). Large effects were demonstrated in two of these studies (Fasoli et al, 2002; Kehoe Bakshi et al 19911 1 0 1 1 0 1 0 0 0 0 1 1 1 1 1 0 0 11 Fasoli et al (2002) 1 1 1 1 1 1 1 0 0 0 1 1 1 1 1 1 1 0 15 Hall and Nelson (1998) 1 1 1 1 1 1 1 0 0 0 0 1 1 1 1 1 1 0 14 Holubar and Rice (2006) 1 1 1 2 1 1 11 1 0 0 1 1 1 1 1 1 1 18 Hoppe et al 20081 1 1 1 1 1 1 0 0 0 0 1 1 0 1 1 1 0 13 Kehoe and Rice 20161 1 1 2 1 1 1 1 0 0 0 1 1 1 1 1 1 1 17 King (1993) 1 0 1 0 1 1 1 0 0 0 0 1 0 0 1 0 0 0 8 Lin et al (1998) 1 1 1 1 1 1 1 0 0 0 0 1 1 1 1 1 1 0 13 Ma et al (1999) 1 1 1 1 1 1 1 0 0 0 1 1 1 1 1 1 1 0 15 Miller and Nelson (1987) et al (1992) 1 1 1 1 1 1 0 0 0 0 0 0 1 0 1 1 0 0 10 Rice et al 19991 1 1 1 1 1 0 0 0 0 0 1 1 1 1 1 1 0 13 Rice et al 20091 1 1 1 1 1 1 0 0 0 0 1 1 1 1 1 1 0 14 Rice and Renock (2006) 1 1 1 1 1 1 1 1 0 0 0 1 1 1 1 1 1 1 16 Ross and Nelson (2000) 1 1 1 1 1 1 1 0 0 0 0 1 1 1 1 1 1 0 14 Sackaloo et al 20151 1 1 1 1 1 1 0 1 0 0 1 1 1 1 1 1 0 15 Steinbeck (1986) 1 1 1 1 1 1 1 0 0 1 0 1 1 1 1 1 0 0 14 Taylor et al 20181…”
Section: Quality Of Motion: Speed Movement and Reaction Time Movemementioning
confidence: 99%
See 2 more Smart Citations
“…In addition rehabilitation requires consideration of the principles of motor learning [45][46][47][48][49] in order to produce optimal outcomes. These include: the benefits of functional and meaningful activities on the retention of skill; [50][51][52] the use of functional tasks [50][51][52]; the need for task specificity where the rehabilitation components focus on the desired outcome (in this case being able to maintain balance in standing and respond to perturbations of balance); and the need for high levels of repetition and balance [53,54]. Balloon volleyball aligns to these key principles.…”
Section: Assessing Therapy Requirements: Stakeholder Inputmentioning
confidence: 99%